2013
DOI: 10.1016/j.jvs.2013.02.241
|View full text |Cite
|
Sign up to set email alerts
|

Reduced hind limb ischemia-reperfusion injury in Toll-like receptor-4 mutant mice is associated with decreased neutrophil extracellular traps

Abstract: Objective Ischemia-reperfusion (IR) injury is a significant problem in the management of patients with acute limb ischemia (ALI). Despite rapid restoration of blood flow following technically successful open and endovascular revascularization, complications secondary to IR injury continue to occur and limit clinical success. Our aim was to create a murine model of hind limb IR injury to examine the role of Toll-like receptor-4 (TLR4) and to determine whether inactive TLR4 led to a decrease in the detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 39 publications
2
47
0
2
Order By: Relevance
“…Both prolonged and transient ischemia induce some muscle tissue damage relative to these uninjured controls, but prolonged ischemia (BAO) appeared to affect the forepaw muscles to a slightly greater degree as evidenced by more extensive muscle fiber degeneration and muscle atrophy compared to the I/R condition. Although both ischemic injuries do not severely alter the muscles, our results are consistent with other reports of muscle tissue integrity during these types of artery occlusions 8,19,47,49 . To then confirm that our occlusion surgeries were not causing direct injury to the sensory neurons, we also analyzed ATF3 staining (a marker of neuronal injury) in the C8 DRGs in mice that underwent BAO or I/R.…”
Section: Resultssupporting
confidence: 93%
“…Both prolonged and transient ischemia induce some muscle tissue damage relative to these uninjured controls, but prolonged ischemia (BAO) appeared to affect the forepaw muscles to a slightly greater degree as evidenced by more extensive muscle fiber degeneration and muscle atrophy compared to the I/R condition. Although both ischemic injuries do not severely alter the muscles, our results are consistent with other reports of muscle tissue integrity during these types of artery occlusions 8,19,47,49 . To then confirm that our occlusion surgeries were not causing direct injury to the sensory neurons, we also analyzed ATF3 staining (a marker of neuronal injury) in the C8 DRGs in mice that underwent BAO or I/R.…”
Section: Resultssupporting
confidence: 93%
“…Savchenko et al [28] demonstrated that extracellular chromatin released through NETosis exacerbates myocardial ischemic-reperfusion injury. Oklu et al [29] demonstrated that hind-limb ischemia-reperfusion injury is reduced in Toll-like receptor-4 mutant mice that are characterized by decreased NET formation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the generation of neutrophil extracellular traps (NETs), an event strictly associated with the activation of autophagy pathway in inflammatory leukocytes 48 and modulated by the recognition of apoptotic cells, 49 has been described in the muscle upon ischemia-reperfusion injury. 50 Further studies will evaluate the relevance of NET contribution to muscle remodeling during autoimmune diseases and in homeostatic conditions.…”
Section: Unique Immune Privileges Of the Skeletal Musclementioning
confidence: 99%